Gendered attitudes toward climate change among geography students at University Namibia (Journal for Studies in Humanities and Social Sciences, 2019)
Students are considered to be a key to dealing with climate change. Their knowledge influences their attitudes, which affects their actions. The degree to which students are likely to engage with climate change depends on their attitude towards climate change. This study investigated gendered attitudes towards climate change of geography students at the University of Namibia. Using a 14-item questionnaire, a total of 56 male and 64 female students from the University of Namibia were surveyed. The results show that students have a generally positive attitude towards climate change. There is, however, a slight difference in the gendered attitudes with regards to the concern over the occurrence of climate change; on how well they think they are informed; who should be responsible for fixing climate change; and whether or not the students felt personally responsible for the occurrence of the phenomenon. It is recommended that the education system be purposely designed to influence students’ attitude for better future decision making in relation to climate change because a person’s attitude forms a fundamental framework for a meaningful way of thinking.